2013
DOI: 10.3126/ajms.v3i3.7744
|View full text |Cite
|
Sign up to set email alerts
|

Perception And Knowledge Regarding Reproductive Health Among Adolescent Males Of Lalitpur

Abstract: Background: Puberty is a significant phase of human growth. It has important implications for the development of regulatory competence and of physical, emotional, social maturity. Adolescents should have knowledge regarding their physical growth and reproductive health, so that unnecessary reservations and stress could be avoided. Adolescent males have as many health issues as adolescent females, but they are less likely to be seen in a clinical setting due to both individual factors and the health care system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…The present study shows that more than half (53.4%) of adolescents had adequate knowledge on sexual and reproductive health, which is consistent with the earlier study [15] that overall knowledge and the perception of adolescents on reproductive health was satisfactory. This study revealed that male adolescents had higher knowledge than females, which is contradictory with the finding of Sutan R [16] the mean knowledge score was (37.32± 2.967) with a significant difference for gender.…”
Section: Discussionsupporting
confidence: 92%
“…The present study shows that more than half (53.4%) of adolescents had adequate knowledge on sexual and reproductive health, which is consistent with the earlier study [15] that overall knowledge and the perception of adolescents on reproductive health was satisfactory. This study revealed that male adolescents had higher knowledge than females, which is contradictory with the finding of Sutan R [16] the mean knowledge score was (37.32± 2.967) with a significant difference for gender.…”
Section: Discussionsupporting
confidence: 92%
“…These questionnaires were developed by reviewing related works of literature thoroughly and were validated before conducting the study. The sample size was calculated using the relation: n = (z)2 p ( 1 -p ) / d2 where n = sample size; z = level of confidence according to the standard normal distribution; p = estimated proportion of the population that presents the characteristic and d = tolerated margin of error [11,12]. The study was conducted only after approval from the Institutional Review Committee of Nagarik College of Health Science.…”
Section: Methodsmentioning
confidence: 99%